Factor the coefficients:
-12=(-1)(3)(2^2)
-9=(-1)(3^2)
3=3
The greatest common factor (GCF) is 3
Next we find the GCF for the variable x.
x^4
x^3
x^2
The GCF is x^2.
Next GCF for variable y.
y
y^2
y^3
the GCF is y
Therefore the GCF is 3x^2y
To factor this out, we need to divide each term by the GCF,
(3x^2y)(−12x4y/(3x^2y) − 9x3y2/(3x^2y) + 3x2y3/(3x^2y) )
=(3x^2y)(-4x^2-3xy+y^2)
if we wish, we can factor further:
(3x^2y)(y-4x)(x+y)
Answer:
A
Step-by-step explanation:
The correct answer will be A
Have a great day
Answer:
If I'm correct, the answer is 1296.
Step-by-step explanation:
6 x 6 x 6 x 6 = 1296
The distance formula is the square root of (X2 - X1)^2 + (y2 - y1)^2. Let D = y and c = x. Plug in the numbers now. Your equation is now the square root of ( -3 - (-5)) ^2 + (-2 - (-4))^2. Now complete it, your answer is 2.82...
Answer and explanation:
Statement - If the difference of two numbers is even then so is their sum.
Let the two even numbers be '2m' and '2n' with m and n are integers.
The difference of two number is
![2m-2n=2(m-n)](https://tex.z-dn.net/?f=2m-2n%3D2%28m-n%29)
Now, The sum of the numbers is
![2m+2n=2(m+n)](https://tex.z-dn.net/?f=2m%2B2n%3D2%28m%2Bn%29)
Let
where k is an integer
Then,
which is also an even number as 2 is multiplied with it.
So, If the difference of two numbers is even then so is their sum.
For example -
Let two even number 2 and 4.
The difference is
, 2 is even.
The sum is
, 6 is even.